2017
DOI: 10.1002/jbm.a.36152
|View full text |Cite
|
Sign up to set email alerts
|

Low‐thrombogenic fibrin‐heparin coating promotes in vitro endothelialization

Abstract: Long-term performance of implanted cardiovascular grafts can be ensured if living endothelium overgrows their surface. Surface modifications to implants are therefore being sought that can encourage endothelialization while preventing thrombus formation until the natural endothelium is formed. In the present study, heparin was covalently attached to a fibrin mesh grown from a polyvinyl chloride (PVC) substrate surface by the catalytic action of surface immobilized thrombin on a fibrinogen solution. The coating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 40 publications
2
27
0
Order By: Relevance
“…In contact with heparinized blood in a Chandler loop or a ow loop model mimicking human blood ow, the coatings suppressed thrombin generation, platelets and leukocyte activation, complement activation and blood clot formation. 29,40 The results presented herein indicate that the binding of GFs preserve the excellent hemocompatibility of the Fb/Hep coating.…”
Section: Hemocompatibility Of the Coatingsmentioning
confidence: 62%
See 2 more Smart Citations
“…In contact with heparinized blood in a Chandler loop or a ow loop model mimicking human blood ow, the coatings suppressed thrombin generation, platelets and leukocyte activation, complement activation and blood clot formation. 29,40 The results presented herein indicate that the binding of GFs preserve the excellent hemocompatibility of the Fb/Hep coating.…”
Section: Hemocompatibility Of the Coatingsmentioning
confidence: 62%
“…28 We have previously shown that a covalent binding of periodate activated heparin to a brin mesh prepared on PVC sheets prevented the formation of a blood clot on the sheets exposed to human blood in a Chandler loop model. 29 The present work aims to develop a surface modication that might accelerate the in vitro and in situ endothelialization of cardiovascular gras while suppressing acute thrombosis. The modication of standard ePTFE gras with a brin mesh decorated by the covalently bound heparin and noncovalently bound FGF and VEGF presented in this work fulls both requirements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite numerous scientific efforts, especially in cardiology, it has not yet been possible to develop optimized anti-thrombogenic vascular implants. Regardless of a series of promising results in vitro [ 31 33 ], these coatings have not yet been successfully transferred to an endovascular device. Although the coating materials used to date for the coating of stents and flow diverters have bio- and haemo-compatible properties [ 32 , 34 ], DAPT is still necessary.…”
Section: Discussionmentioning
confidence: 99%
“…[42] Since alginate hydrogels impede endothelial cell adhesion, we upgraded the alginate matrix with the natural polymer fibrin being known for its various adhesion sites for endothelial cells [18] and its high biocompatibility as a stent coating material [4,6] or vascular graft. [18,43] Furthermore, Fe-NPs have been shown to reinforce the fibrin matrix and to enhance endothelial cell proliferation. [13,15,44] On the whole, we hypothesize based on available literature that Fe-NP enriched alginate-fibrin hydrogels synergize their individual antithrombotic properties to a compound highly hemocompatible stent coating material.…”
Section: Hemocompatibility Of Alginate-fibrin Hydrogels Enriched With Iron Nanoparticlesmentioning
confidence: 99%